The Role of Pedagogy and Learning Environment in Shaping Students’ Interest in Tourism Education - Andreas Suwandi; Rini Andari; Nadhia Maesari; Ariel Putri Utami (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
The background of this research is based on the learning attitude and conditions of the students in the Dasar-Dasar Keahlian class. The attitude is reflected in the lack of enthusiasm during the lesson, which is indicated by distracted student performances as they engage more with their smartphones, are in a sleepy state, communicate with each other, excuse themselves to the bathroom, and other reasons. These conditions show the low learning interest amongst the students, which motivates me to conduct a research regarding the factors that affect their learning interest. The main objective of this research is to identify the causal factors of students’ interest in learning. Acknowledging the factors can result in an effective learning environment that corresponds with the students’ interest, therefore the number of negligent students could be diminished. The method used in this research is a qualitative approach with descriptive research methods which are conducted via observation in class during learning activities, interviews, questionnaires, and documentations. This research involved 33 students from the class of X PH 1 in SMK Bina Warga Bandung, as well as the vice principal, the chief of Hotel Accomodation Program, and the teacher of Hotel Productivity. The result of this research shows that there are internal and external factors that affect the students’ learning interest during the class period of Dasar-Dasar Keahlian. The internal factors include students’ level of intelligence factor, talent factor, and passion factor, while the external ones are school factor, familial factor, and students’ socio-environmental factor.